2006
DOI: 10.1136/bjsm.2006.025924
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of injury in amateur and professional boxing

Abstract: Background: There is concern over the potential for a high incidence of injury in boxing. This is despite a lack of prospective data evaluating the risk for modern day participants. Updated, reliable data with a focus on potential exposure to injury for both amateur and, especially, professional boxers is required. Aim: To determine the epidemiology of injury and exposure of amateur and professional boxers in Victoria, Australia. Methods: A prospective cohort study with one year follow up was carried out over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 34 publications
2
87
1
7
Order By: Relevance
“…An earlier 6-month investigation analyzed the prevalence of injuries in amateur and professional combat athletes, and found an incidence of 42.9% 25 . Although physical contact is high in combat sports, a cohort study with professional boxers showed a lower incidence than in team sports such as soccer, professional rugby, hockey and basketball, suggesting that the incidence of injuries is related to the intensity at which the sport is played 25 , as well as the large number of impacts in areas of the body prone to torn ligaments, overuse and sudden changes in direction 26 . As such, they are strongly dependent on the type of sport and the competitive stage of the athlete.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier 6-month investigation analyzed the prevalence of injuries in amateur and professional combat athletes, and found an incidence of 42.9% 25 . Although physical contact is high in combat sports, a cohort study with professional boxers showed a lower incidence than in team sports such as soccer, professional rugby, hockey and basketball, suggesting that the incidence of injuries is related to the intensity at which the sport is played 25 , as well as the large number of impacts in areas of the body prone to torn ligaments, overuse and sudden changes in direction 26 . As such, they are strongly dependent on the type of sport and the competitive stage of the athlete.…”
Section: Discussionmentioning
confidence: 99%
“…Most injuries in boxing, both amateur and professional, occur during competition (57%), compared with training (43%). 4 The authors of 1 cohort study reported an injury rate of 1.0 injury per 1000 hours of participation for amateur boxers (15.1-37.1 years of age). 4 This rate is actually lower than reported high school athlete injury rates of 4.4 per 1000 athlete-exposures in football, 2.5 in wrestling, and 2.4 in soccer.…”
Section: Boxing-related Injuriesmentioning
confidence: 99%
“…4 The authors of 1 cohort study reported an injury rate of 1.0 injury per 1000 hours of participation for amateur boxers (15.1-37.1 years of age). 4 This rate is actually lower than reported high school athlete injury rates of 4.4 per 1000 athlete-exposures in football, 2.5 in wrestling, and 2.4 in soccer. 16 Intentional facial and head injuries, however, are more frequent in boxing.…”
Section: Boxing-related Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even with the use of protective headgear the incidence of mild traumatic brain injury (mTBI) known as concussions have not, and continue to be a concern in both recreational and professional sports [2][3][4][5]. A recent survey reported 110 in 100,000…”
Section: Introductionmentioning
confidence: 99%